Polymorphism analysis of canine olfactory gene cOR52H9 and evaluation of its relation to odor detection performance by police dogs - Thu, Do Van; Binh, Doan Viet; Chi, Nguyen Trong; Phong, Le Xuan; Hung, Nguyen Ngoc; Hue, Le Thi; Khoi, Tran Xuan; Ninh, Vo Thi (Academia Journal of Biology, 2016)
The recruitment of professional dog training to date rely on the external appearance of the dog. Among selected to train dogs to detect drugs, explosives, as a result only about 30% of trained dogs are satisfied with training. COR52H9 gene is located on chromosome 21, coding for olfactory receptors located on the surface of neuroepithelium in the nasal cavity, have an important role in identifying odors. In this report, we present the results of polymorphism studies of olfactory receptor gene cOR52H9 and its relation to odor detection performance of Berger dogs. Blood samples of 28 dogs (Canis lupus familiaris) of Administration Department management, training and professional use of animals - Ministry of Public security has been collected for the Isolation and Analysis of the correlation between genotype and phenotype. Isolated gene has more than 99% homology with the gene sequence registered in gene banks. There are 5 SNPS detected: T87A, G370A, T414G, G450A and G814T. Moderate correlations between genotype and drug detection performance of dog were identified in T414G, G450A (p = 0.002, r = 0.554) and G814T (p = 0.007, r = 0.498). Combined use of these SNPs selected will be the dogs have the ability to detect odors best for training detect drugs.   Citation: Do Van Thu, Doan Viet Binh, Nguyen Trong Chi, Le Xuan Phong, Nguyen Ngoc Hung, Le Thi Hue, Tran Xuan Khoi, Vo Thi Ninh, 2017. Polymorphism analysis of canine olfactory gene cor52h9 and evaluation of its relation to odor detection performance by police dogs. Tap chi Sinh hoc, 39(1): 102-107. DOI: 10.15625/0866-7160/v39n1.7130. *Corresponding author: dvietbinh@yahoo.com Received 22 September 2015, accepted 20 March 2017